(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This article presents the concept of interpretation, hermeneutics, and the reception of the literary text in the consciousness of the reader, which is at the center of the problematic field of literary science. Awareness of the locality of traditional interpretation methodologies leads to the search for other ways of interpreting artistic work. At the present stage of development of literary science, paying attention to the communicative function of literary text, such an interpretive methodology is relevant, which would allow to fully explore the work from the standpoint of an aesthetic dialogue between the author, the text, and the reader. James Joyce’s Ulysses represents one of the most complicated works that was written in modern English and world literature and that contributed implicit and explicit interpretation and meaning to the original text.